THE REALITY OF THE RELATIONSHIP BETWEEN AGRICULTURAL RESEARCH AND EXTENSION ORGANIZATIONS IN IRAQ - Anan Al-Ansari; Tamer Al-Janab; Jamal Alotaibi (Arab Universities Journal of Agricultural Sciences, 2020)
Iraq is one of the agricultural countries in the world. Agriculture is the second source of income after oil in Iraq. Agricultural development is a link between scientific research and agricultural extension because the use of scientific knowledge in agriculture has become very important, which has prompted many countries to increase their investment in scientific research. There is a main agricultural extension department in Baghdad, in addition to agricultural extension departments in the provinces. The aim of this study was to determine the actual relationship between the agricultural research and extension organizations in Iraq throw knowing the importance of activities that achieve the relationship and implementation level according to respondents' opinions. The study aimed also to identify the barriers facing the relationship between the agricultural research and extension organizations and respondents' suggestions that strength the link between the researches and agricultural extension agents. This study was conducted on group of researchers and extension agents who work in Agricultural Extension and Cooperation Department and Agricultural Researches Department. A random sample of 40% was selected. The total was (38) agricultural extension agents and (35) agricultural researchers. A questionnaire was used as a tool for data collection. Data were analyzed using the SPSS Version 24.0 statistical software. Descriptive statistics including percentages, frequencies, means, and standard deviations, were used to summarize the data. The most important results showed that the relationship between agricultural research and extension organizations was weak, while a high percentage of respondents believed that the relationship between them was very important. The study illustrated that the most important barrier facing the relationship between the agricultural research and extension organizations was the absence of regulations and laws that organize the relationship between them. The most important suggestions that respondents believed to strengthen the relationship are the establishment of legislations that organize the relationship and work through the research and extension teams and establishment of permanent committees to coordinate the work between them. In addition, the study found that the communication between agricultural researchers and extension agents was informal. Furthermore, the study recommended that the relationship should be continued, and that multiple organizational and administrative methods should be used to strengthen the linkages between agricultural research and extension organizations. Also, the study recommended that agricultural researchers and extension agents should participate in planning and implementing agricultural extension programs.